Phase I study of nintedanib in Japanese patients with advanced hepatocellular carcinoma and liver impairment. Issue 12 (12th December 2016) - Okusaka, Takuji; Otsuka, Taiga; Ueno, Hideki; Mitsunaga, Shuichi; Sugimoto, Rie; Muro, Kei; Saito, Isao; Tadayasu, Yusuke; Inoue, Kohei; Loembé, Arsene‐Bienvenu; Ikeda, Masafumi
Abstract : This phase I, dose‐escalation study evaluated the safety, preliminary efficacy and pharmacokinetics of nintedanib, a triple angiokinase inhibitor, in Japanese patients with advanced hepatocellular carcinoma and mild/moderate liver impairment. Thirty patients with unresectable hepatocellular carcinoma were enrolled to groups, depending on whether liver impairment was mild (group I, aspartate aminotransferase and alanine aminotransferase ≤2× upper limit of normal and Child–Pugh score 5 [ n = 14] or 6 [ n = 2]) or moderate (group II, Child–Pugh score 5–6 and aspartate aminotransferase or alanine aminotransferase >2× to ≤5× upper limit of normal [ n = 7] or Child–Pugh score 7 [ n = 7]); 22 patients had prior sorafenib treatment. Nintedanib was given twice daily in 28‐day cycles until disease progression or unacceptable adverse events, starting at 150 mg (group I) or 100 mg (group II) and escalating to 200 mg. The primary objective was to define the maximum tolerated dose based on occurrence of dose‐limiting toxicities during cycle 1 (grade ≥3 non‐hematological and grade 4 hematological adverse events). No dose‐limiting toxicities were reported during cycle 1 and the maximum tolerated dose for both groups was 200 mg twice daily. The most frequent adverse events were gastrointestinal (diarrhea, nausea, vomiting, and decreased appetite). No patients discontinued nintedanib due to adverse events; 31% of group I and 21% of group II had dose reductions. Median time to progression was 2.8 months (95% confidence interval, 1.05–5.52) for group I and 3.2 months (95% confidence interval, 0.95–6.70) for group II. Nintedanib showed a manageable safety profile and efficacy signals, including in patients previously treated with sorafenib. Clinical trial registration NCT01594125; 1199.120 (ClinicalTrials.gov). Abstract : In this phase I trial in Japanese patients with advanced hepatocellular carcinoma and mild/moderate liver impairment, nintedanib demonstrated a manageable safety profile, both in patients who had received prior treatment with sorafenib and those that had not. The maximum tolerated dose of nintedanib was established to be 200 mg twice daily, regardless of whether patients had mild or moderate liver impairment.